Écrire nègre en français : Affaire „Batouala” - Kalinowska, Ewa (Acta Universitatis Lodziensis. Folia Litteraria Romanica, 2014)
Batouala: A True Black Novel, written in 1921 by René Maran, was the first black narrative in French to win the Prix Goncourt. Written nearly twenty years before Senghor’s and Cesaire’s works appeared, Batouala stands out as a notable novel which foretells the Negritude phenomenon expressing the validation of Africa as the matrix of a proud Black race. The Blacks’ world and attitudes are portrayed through their beliefs and habits. The contact of African and European cultures is a traumatic one – Africans present a candid portrayal of colonialist presence in their country – critical and raw. Despite the discomfiture of the encounter between two cultures, Batouala paved the way for the successors – Negritude’s representatives, writers of the independence period and engaged witnesses of the modernity.